ANALISIS PENGARUH TINGKAT DISPOSABLE INCOME, TINGKAT RELIGIUSITAS TERHADAP MINAT MENABUNG DI BANK SYARI’AH BERBASIS DIGITAL - Tirtha Syaputra; Dwisari, Indri; Galingging, Nabilah Hanifah (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2024)
The growth and development of Islamic banking is quite rapid because it adheres to Islamic principles, one of which is the prohibition of usury in all forms of transactions. Factors that can influence consumption are disposable income and the level of religiosity and are supported by developments in the field of banking digitalization. This study aims to determine whether there is a partial and simultaneous influence between Disposable Income and the Level of Religiosity on the Interest in Saving in Digital-Based Islamic Banking. This study uses a quantitative method. The sampling technique in this study is Random Sampling using the Slovin formula. Data collection was carried out by distributing questionnaires with a sample of 44 respondents at Madrasah Ibtidaiyah As-Sidiqiyah Siak. To analyze using an analysis tool, namely SPSS Ver. 29.0. The analysis method uses classical assumption tests, validity and reliability tests, hypothesis tests, multiple linear regression tests, and determinant coefficient tests. The results of the study showed that there was a significant partial influence of disposable income on the savings interest of MI As-Sidiqiyah Siak Teachers in Islamic banking with a calculated t value (7.747) > t table (1.683) with a p-value (0.001). The variable of religiosity level had a significant partial influence on the savings interest of MI As Sidiqiyah Teachers in Islamic banking with a calculated t value (6.515) > t table (1.683) with a p-value (0.001). The simultaneous test showed that there was a significant simultaneous influence of disposable income and religiosity level on the savings interest of MI As-Sidiqiyah Siak Teachers in Islamic banking with a calculated F value (54.664) > F table (3.23) with a p-value (0.000).